Highly crystalline LiCuXFe1-XPO4 nanoparticles synthesized by high temperature thermal decomposition: A morphological and electrical transport study - Martinez, Pablo Sergio; Ruiz, Fabricio Carlos; Curiale, Carlos Javier; Vasquez Mansilla, Marcelo; Zysler, Roberto Daniel; Dada, L.; Moreno, Mario Sergio Jesus; Rodriguez, Luis Miguel; Fregenal, Daniel Eduardo; Bernardi, Guillermo Carlos; Lima, Enio Junior (IOP Publishing, 2016)
Fil: Martinez, Pablo Sergio. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Patagonia Norte; Argentina. Comisión Nacional de Energía Atómica. Gerencia del Área de Energía Nuclear. Instituto Balseiro; Argentina. Universidad Nacional de Cuyo; Argentina